EVALUASI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN PANDAN (Pandanus amarryllifolius Roxb) TERHADAP Bakteri Staphylococcus aureus dan Escherichia coli - dahlan ahmad (UNISBA Press, 2023)
Pandan Wangi (Pandanus amaryllifolius Roxb) in the surrounding community is often processed as a sourceof cooking/cake ingredients because of its fragrant aroma, therefore the leaves are often used as a foodingredient, but the community does not know much about the potential of this fragrant pandan which canactually be used. as one of the drugs is antibacterial. The purpose of this study was to determine the activityof pandan leaf extract against Stpahylococcus aureus and Escherichia coli bacteria. The method used in thisstudy was well diffusion with invitro test, so that MIC was obtained with a concentration of 15%, namely4.98 mm with weak antibacterial activity, while in comparison with Cefadroxil monohydrate 2.5%, namely28.06 mm with very strong antibacterial activity.